On haptic media and the possibilities of a more inclusive interactivity. (October 2017) - Paterson, Mark
What is the relationship between the 'haptic' and the 'tactile' when it comes to media? We might question whether there is such a thing as 'haptic media'; in other words, is there a type of media that invite the attention of one modality rather than another, or that foster certain types of interaction over others? If we were to speak about 'haptic media', to what extent does it engage directly (only) with touch, and to what extent does it involve some form of enhancement of another modality? In what ways can haptic media appeal beyond the visuocentric norm of the screen, and therefore to non-normate or disabled users? Further, to what extent does the haptic in particular benefit from 'sensory substitution', which is most usually of touch for vision in assisted living technologies for the blind, or of sound for touch for the deaf, for example? Certain historical instances of sensory substitution systems are discussed below, including Norbert Wiener's 'hearing glove' and Bach-Y-Rita's tactile–visual sensory substitution (TVSS) system, to make a larger argument about the role of haptic technologies, and haptic media, for more inclusive digital interactions.